PERAN UNIVERSITAS NEGERI (UIN) MENYONGSONG KEBANGKITAN TRADISI KEILMUAN ISLAM - Jalaluddin Jalaluddin (Conciencia, 2014)
Abstract:Transformation of the State Islamic Institute (IAIN) to the State Islamic University (UIN), can be seen as a necessity of history and civilization. The process of transformation of higher education institutions of Islam is actually already happened several times. Beginning of the institutional status of official academy Ministry of Religious Affairs, the Department of Religious Science Academy name (ADIA).First, the presence of UIN faced with the global era and the third millennium. Global era marked by the rise of science and technology. Along with it, social thought and humanities dealing with a new outlook, known as postmodernism, poststructuralism (Franz Dahler and Eka Budianta, 2000: 84). The third millennium is characterized by a shift in the value system that refers to the permissiveness (permissive).         Secondly, with this transformation UIN faced with the preparedness to meet new status bears, namely the university. These changes however, needs to be supported by changes in patterns and ways of thinking of the Pengola or academicians who preceded by paradigm change.     Building kelimuan tradition is a milestone in the development of the supporting values of Islam in the realm of civilization built on the UIN. The formation of the scientific tradition directly related to the values contained in the primary sources of Islam, namely the Qur'an and Hadith.         UIN realization through the transformation process at least not limited to institutional alone. Moreover UIN also required to develop themselves, to change the paradigm, the paradigm refers to the Qur'an (derived from the values of the teachings of the Qur'an), as was done by Muslim scientists Classical era in building the Islamic scientific tradition . Muslim scientists motivated motivated by the values of the teachings of the Qur'an. At least realized, that a system of doctrine, not useful, and it will not bring good life promised, if not implemented (Majid, 1992: xiv- xivi). Keywords: UIN, the transformation of science, the